THE ROLE OF COGNITIVE RESTRUCTURING TECHNIQUES IN IMPROVING EMOTIONAL REGULATION AFFECTED BY TECHNOSTRESS (Retrospective Case Study of Guidance and Counseling Study Program Students Class of 2020 at PGRI Banyuwangi University): PERANAN TEKNIK RESTRUKTURISASI KOGNITIF DALAM MENINGKATKAN REGULASI EMOSI YANG TERDAMPAK TECHNOSTRESS (Studi Kasus Retrospektif Mahasiswa Prodi Bimbingan dan Konseling Angkatan 2020 di Universitas PGRI Banyuwangi) - Febrianti Srimelani; Siti Napisah; Ratna Wulandari (Program Studi Bimbingan dan Konseling, 2024)
Technostress is an impact of technology that produces stressful conditions, due to the flow of technology that continues to develop and run which makes technology users unable to organize activities and manage themselves. So that the formulation of the problem: What factors can cause emotional regulation in students to be low towards the use of technology and How to role of Cognitive Restructuring techniques in improving the ability to manage student emotional regulation in dealing with technostress? The method used in this study uses qualitative research methods with the type of Retrospective Case Study. Data collection techniques used are observation, interviews and documentation. The data that has been obtained is collected to find the validity of the data using data triangulation, data presentation and drawing conclusions from the research that has been carried out. The results showed that there are symptoms of technostress triggering factors, liked Techno Invasion and Techno Overload to other factors that can affect the ability to regulate emotions in a person, including stressors, age factors, cognitive zelazo, social and cultural aspects, so factor gives encouragement to technology users be dependent on the use of technology itself. The role that can be done to improve the ability to manage emotional regulation in the face of technostress itself can be given treatment as a intervention to reduce addiction to technology. The role of cognitive restructuring techniques in the CBT approach is needed to change the behavior of technology users to control and reduce the use of technology itself.